2013
DOI: 10.1038/nature11940
|View full text |Cite
|
Sign up to set email alerts
|

Multiple phases of chondrocyte enlargement underlie differences in skeletal proportions

Abstract: Even a casual pass through the great halls of mammals in the world’s natural history museums highlights the wide diversity of skeletal proportions that allow us to distinguish between species even when reduced to their calcified components. Similarly each individual is comprised of a variety of bones of differing lengths. The largest contribution to the lengthening of a skeletal element, and to the differential elongation of elements, comes from a dramatic increase in the volume of hypertrophic chondrocytes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
312
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 336 publications
(342 citation statements)
references
References 29 publications
13
312
2
1
Order By: Relevance
“…While previous studies have found the importance of volume regulation by chondrocytes in cartilage physiology 4244 , our work demonstrates that chondrocytes utilize changes in volume to sense the viscoelastic properties of their microenvironment. In adherent cells, it is known that cells sense viscoelasticity through exerting traction forces at integrin-ECM ligand adhesions, gauging resistance to traction forces, and clustering ligands 18,4548 .…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…While previous studies have found the importance of volume regulation by chondrocytes in cartilage physiology 4244 , our work demonstrates that chondrocytes utilize changes in volume to sense the viscoelastic properties of their microenvironment. In adherent cells, it is known that cells sense viscoelasticity through exerting traction forces at integrin-ECM ligand adhesions, gauging resistance to traction forces, and clustering ligands 18,4548 .…”
Section: Discussionmentioning
confidence: 47%
“…This impact of stress relaxation on chondrocyte cell volume expansion in hydrogels for 3D culture was found in alginate hydrogels and confirmed in PEG and agarose hydrogels. The size of chondrocytes in fast relaxing hydrogels was larger than chondrocytes in mature hyaline cartilage 42 , but smaller than hypertrophic chondrocytes in the deep zone of hyaline cartilage. We note that there could be multiple pathways by which chondrocytes can be induced to form large amounts cartilage matrix.…”
Section: Discussionmentioning
confidence: 78%
“…The investigators in this work described growth of the hypertrophic chondrocytes as progressing through three distinct phases and the IGF-1 conditional knockouts had a defect in the last or third phase, which led to the hypertrophic chondrocytes not increasing in size. 34 The difference in size of the chondrocytes that have a loss in IGF-1 has also been observed with the global IGF-1 deletion. This fact is particularly interesting taking into account the fact that mTOR signaling can be activated by IGF-1 signaling and is active during growth plate development also has been shown to regulate cell size.…”
Section: Igf-1 and Chondrocytesmentioning
confidence: 91%
“…The mice with an osteocyte-specific knockout also have a shorter growth plate compared with the wild-type control along with smaller hypertrophic chondrocytes. 34 There is expression of the IGF1R on osteoclasts and during bone remodeling. Matrix IGF-1 had been shown to be necessary for MSC differentiation, although whether osteoclasts secrete IGF-1 is not clear.…”
Section: Igf-1 Osteocytes and Osteoclastsmentioning
confidence: 99%
“…proximal versus distal tibia) [125]. Furthermore, differences in cell size largely explain the differences in growth rate between mammal species as evidenced by large hypertrophic chondrocytes of the bat forelimb elements [126] and metatarsals of the three-toed jerboa [127] compared with homologous anatomical positions in the mouse. By contrast, birds vary growth plate cell number to control skeletal proportions [128].…”
Section: Evolution Of Limb Segment Proportion In Mammalsmentioning
confidence: 99%